2017
DOI: 10.1155/2017/6456070
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of Design Formulae for Equivalent Elasticity of Masonry Structures Made with Bricks of Low Modulus

Abstract: Bricks of low elastic modulus are occasionally used in some developing countries, such as Indonesia and India. Most of the previous research efforts focused on masonry structures built with bricks of considerably high elastic modulus. The objective of this study is to quantify the equivalent elastic modulus of lower-stiffness masonry structures, when the mortar has a higher modulus of elasticity than the bricks, by employing finite element (FE) simulations and adopting the homogenization technique. The reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…9). [8] [1] was observed that typical mortar has a lower elasticity than bricks in the homogenization process (Table 1). His proposed analytical approach can significantly contribute to a safer analysis and design of masonry structural systems built with low-quality bricks in various developing countries, such as Indonesia.…”
Section: Figure 7 Average Bricks Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…9). [8] [1] was observed that typical mortar has a lower elasticity than bricks in the homogenization process (Table 1). His proposed analytical approach can significantly contribute to a safer analysis and design of masonry structural systems built with low-quality bricks in various developing countries, such as Indonesia.…”
Section: Figure 7 Average Bricks Compressive Strengthmentioning
confidence: 99%
“…The general Indonesia people had known that buildings made from wood are resisted to the effect of seismic loading. In fact, in every region of Indonesia, almost 80% use bricks as the primary material of masonry [1]. In some developing countries, traditional clay bricks are produced locally without following any technical inspection or standard and the quality varies from region to region.…”
Section: Introductionmentioning
confidence: 99%
“…Limestone West Sumatra is one of the province in Indonesia that is prone to earthquakes [1]. However, more than 80% of either residence or office buildings used bricks which are produced do not meet the Indonesian Industrial Standard (SNI) of 15-2094-2000.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is in a seismic area and frequently suffers earthquakes and fires. It can learn a lesson in Indonesia that the brick walls are always crashed by earthquakes [1,2,3]. Many efforts have been made to mitigate the damage and retrofitting is one of the approaches for improving structural safety after earthquakes.…”
Section: Introductionmentioning
confidence: 99%